The shortcomings of the income and asset declaration system in Jordan illicit enrichment law - Abu-Morad, Mohannad Ahmad; Mohd Noor, Fauziah; Ayub, Zainal Amin (2016)
This article discusses the Jordanian Income and Asset Declaration (AID) system or what socalled the financial disclosure.This study intends to highlight the Jordan Illicit Enrichment law, which is the legal framework of the AID system in line with the international criteria and guide lines such as the United Nations Convention Against Corruption (UNCAC), the Organization for Economic Co-operation and Development (OECD) guide lines and the World Bank reports.The IAD system had been adopted in Jordan to monitor the development occurs the public official's wealth aiming to detect and prevent any possibility of illicit enrichment.but, what is the efficiency of the law on the real practical? Actually, a few problems invalidate the role of IAD in fighting corruption; such as the legal inadequacy and contradiction with other legislations that prevent the enforcement of law, thereby, these shortcomings disable the real objectives of the law. Thus, this study tries to explain these problems within the Jordanian legal framework, aiming to introduce convenient suggestions.